Telehomecare technology across sectors: claims of jurisdiction and emerging controversies - Dinesen, Birthe (Igitur, Utrecht Publishing & Archiving, 2007)
PURPOSE: The purpose of this study was to explore and identify inter-organisational and inter-professional controversies that emerge when telehomecare technology is implemented across healthcare sectors. THEORY: A combined inter-organisational and inter-professional perspective constitutes the conceptual framework for this study. METHODS: The case study approach was applied as the overall methodology of the study. A triangulation of data collection techniques was used in order to provide multiple sources of evidence for exploring and identifying controversies (documents, participant observation, qualitative interviews, focus group interviews). FINDINGS: During the design and implementation phases of a telehomecare system, several types of controversies emerged as part of the inter-organisational and inter-professional agenda. These controversies involved competing claims of jurisdiction, controversies over knowledge technologies, or differences in network visions and network architecture. DISCUSSION AND CONCLUSIONS: The identification of such controversies and differences in the design and implementation process of the concept of home hospitalisation for heart patients by means of telehomecare technology can contribute to the uncovering of new knowledge. These issues should be taken into account when initiating a telehomecare project and implementing telehomecare technology. Technology in a network and across inter-professional relations poses a challenge to this new field. There is a particular need to precisely define the claims of jurisdiction, and the accompanying controversies that can arise related to knowledge technologies, network visions and network architecture.